Revisión de bibliografía sobre la gestión de la cadena de suministro y el empleo de la tecnología de identificación por radio frecuencia en productos perecibles - Huamani Ccamaqque, Maradona (2020)
In the context of the present work, a bibliographic review of different academic research articles is presented, referring to the main findings, methods and strategies in the Management of the Supply Chain of perishable products. Likewise, a review was carried out on the latest advances in the application of RFID technology to minimize waste in the supply chain due to the perishability and traceability of these products. Subsequently, a critical analysis corresponding to each topic and a general conclusive analysis were carried out. Where it could be indicated that the main challenge of this type of supply chain is its high level of uncertainty in demand, due to its defined useful life and its variability with respect to the environmental conditions of transport and storage. They are presented as real obstacles in estimating demand, optimal order quantity (stock). On the other hand, the use of RFID technology within the supply chain can significantly help in its management and contribute to better decision-making.